MEMS-Assisted Cryptography for CPI Protection. - English, J.
The authors present a concept for an anti-tamper system that dynamically generates a cryptographic key derived from microelectromechanical systems (MEMS) arrays encapsulated within a protected system in a single package. The system provides protection in active and passive states with no battery backup.
Keywords: MEMS-assisted cryptography; Antitamper system; Critical program information protection; Dynamic cryptographic key generation; Microelectromechanical system